Justiça distributiva e federalismo cooperativo: igualdade federativa como critério norteador para promover partilha dos royalties petrolíferos do pré-sal - Iaci Pelaes dos Reis (2017)
The essential objective of this thesis is to demonstrate how the Brazilian State, as a federation guided by values linked to social justice and the principles of cooperative federalism, constitutionally conformed to the paradigm of the Democratic State of Law, must To share among the federated entities the revenues from the exploitation of pre-salt oil, as a way of realizing the ideals and fundamental objectives of Brazilian society, marked by serious social, regional and economic disparities. In this respect, and considering that oil revenues play an important role in strengthening the financial capacity of the federated entities in order to fund satisfactory social fundamental rights, such as health and education, to promote the sharing of these revenues in the Brazilian Federation. The basic hypothesis that guides this research is that the criterion constitutionally adequate to promote fair sharing of oil royalties is not that of the geographical proximity of the federated unit to the place of extraction of this nonrenewable natural resource, but that of equality between the federated entities Subnational, modulated by a distributive arrangement that ensures financial equilibrium in horizontal federative relations. In this perspective, it is argued that the apportionment of royalties should represent an equitable advantage for all subnational entities and not just for some. Therefore, any distribution that results in unjustified favoritism in favor of certain States and Municipalities is rejected. In order to do so, it is based on an approach of cooperative financial federalism in its interconnection with the idea of distributive justice, in which Brazilian society is viewed as an equitable system of social cooperation and that every Brazilian citizen, as an intrinsic value, deserves Equal consideration. In view of this core idea, after an analysis of Law 12.734/2012 and changes in Law 12.351/2010, it is argued that sharing in reference should be guided by the federative cooperative principle, in its financial dimension, as a conducive mechanism To the achievement of the fundamental objectives of the Brazilian State, including the eradication of poverty and the reduction of social and regional inequalities, in particular through adequate financing of public services, which provides for social inclusion, substantive freedom and the exercise of citizenship In the political-legal sense.